Soil Erosion by Wind in Madurai District - Sivasubramaniam, T. (Journal of Soil and Water Conservation, 2022)
Soil erosion by wind obtains in a serious form in the area between Thevaram and Bodinaickanur in Periakulam Taluk of Madurai District in Madras State. The area lies between 9’55’ and 10’ of the North latitude and 7T 15’ and 773 20’ of the East longitude. The affected area is about eight miles in length from south west to north east with a width ranging from half to three miles west to east. This area is bounded on the west and south by the western ghats, on the east by plain lands and on the north by the Palni range of hills. The area lies adjacent to the western ghats on its eastern side.